Increased structural and combinatorial diversity in an extended family of genes encoding Vlp surface proteins of Mycoplasma hyorhinis - Yogev, D. (The Hebrew University, Jerusalem, Israel.); Watson-McKown, R; Rosengarten, R; Im, J; Wise, K.S (Journal of Bacteriology, 1995)
Variable lipoproteins (Vlp) constitute the major coat protein of Mycoplasma hyorhinis. They are products of multiple, divergent, single-copy genes organized in a chromosomal cluster. Three genes, vlpA, vlpB, and vlpC, have been previously identified in clonal isolates of M. hyorhinis SK76. Each is linked to a characteristic promoter region containing a homopolymeric tract of adenine residues [poly(A) tract], subject to hypermutation, that transcriptionally controls phase variation of vlp genes and leads to combinatorial surface mosaics of distinct Vlp products. The size of the natural vlp gene repertoire is unknown but may critically determine the degree of structural and combinatorial diversity available in this species. In this study, the vlp repertoire of M. hyorhinis GDL-I was characterized and shown to contain three additional genes, vlpD, vlpE, and vlpF, clustered with other known vlp genes in the order 5'-vlpD-vlpE-vlpF-IS-vlpA-IS-vlpB-vlpC-3', where IS represents copies of the IS1221 element of M. hyorhinis. The 5' boundary of this expanded family was identical to that of the more limited family 5'-vlpA-IS-vlpB-vlpC-3' previously described in a clonal isolate of strain SK76. A recombinant construct containing vlpD, vlpE, and vlpF expressed antigenically distinguishable products corresponding to each gene. These genes encode characteristic C-terminal repetitive regions that are subject to size variation by insertion or deletion of intragenic repeats but maintain an extended, charged structure. Each vlp gene also contained characteristic alternative open reading frames, which provide a potential reservoir of coding sequence for Vlp diversity, possibly recruited through insertion and/or deletion mutations. These findings demonstrate a vastly expanded potential for structural diversity and combinatorial display of surface mosaics on this organism.